PECULIARITIES OF DEVELOPMENT OF DIVERGENT THINKING OF PRESCHOOL CHILDREN - Shokirjonova Fotimakhon Murodjon kizi. (Western European Studies, 2024)
This article focuses on issues related to preschoolers, including play, school transitions, and early literacy.
Keywords: Divergent thinking; association; brainstorming